2016
DOI: 10.1038/srep23355
|View full text |Cite
|
Sign up to set email alerts
|

Splice form variant and amino acid changes in MDR49 confers DDT resistance in transgenic Drosophila

Abstract: The ATP-binding cassette (ABC) transporters represent a superfamily of proteins that have important physiological roles in both prokaryotes and eukaryotes. In insects, ABC transporters have previously been implicated in insecticide resistance. The 91-R strain of Drosophila melanogaster has been intensely selected with DDT over six decades. A recent selective sweeps analysis of 91-R implicated the potential role of MDR49, an ABC transporter, in DDT resistance, however, to date the details of how MDR49 may play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…transporters (mdr49, mdr50, mdr65 and FBgn0035695) based on their similarity to the mammalian 'pglycoprotein' transporters implicated in resistance to a wide range of drugs (Sarkadi et al, 2006). Both Mdr49 and Mdr65 have been implicated in DDT resistance in Drosophila (Strycharz et al, 2013;Gellatly et al, 2015;Seong et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…transporters (mdr49, mdr50, mdr65 and FBgn0035695) based on their similarity to the mammalian 'pglycoprotein' transporters implicated in resistance to a wide range of drugs (Sarkadi et al, 2006). Both Mdr49 and Mdr65 have been implicated in DDT resistance in Drosophila (Strycharz et al, 2013;Gellatly et al, 2015;Seong et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The earliest evidence showed that ABCB transporters were over‐expressed in thiodicarb‐resistant larvae of the tobacco budworm, Heliothis virescens , when tested using human monoclonal P‐gp antibodies (Lanning et al ., ). In Drosophila melanogaster , Mdr49 , Mdr50 , Mdr65 and Mrp1 have been reported to be involved in DDT resistance in the 91‐R strain, and injection of double‐stranded RNA mixtures for Mdr50 , Mdr65 and Mrp1 increased susceptibility to DDT in the 91‐R strain (Gellatly et al ., ; Seong et al ., ). Recently, quantification of transcript levels, synergism with inhibitors (such as verapamil and quinidine) and RNA interference studies of mosquitoes have revealed the potential involvement of ABCB transporters in organophosphate and pyrethroid resistance in Aedes sp.…”
Section: Introductionmentioning
confidence: 97%
“…These two strains were derived from a known common origin, but subsequent differences in the DDT selection schemes have provided a valuable resource for comparative analysis within the context of a model for studying xenobiotic resistance mechanisms on a genomic‐wide scale. Indeed, these two strains formed the basis of a comparative genomic study that identified genome regions with significant variance in nucleotide fixation putatively attributable to the effects of differential selection, which included one region encoding Cyp4g1 and ATP‐binding cassette transporters (ABC transporters) open reading frames . Previously, Brandt et al .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these two strains formed the basis of a comparative genomic study that identified genome regions with significant variance in nucleotide fixation putatively attributable to the effects of differential selection, which included one region encoding Cyp4g1 47,48 and ATP-binding cassette transporters (ABC transporters) open reading frames. 47,49 Previously, Brandt et al showed that the P450 inhibitor piperonyl butoxide (PBO) drastically reduces (but does not eliminate) DDT resistance in D. melanogaster, providing further evidence that differential expression of P450 genes is a component of the DDT resistance phenotype. 29 The current study expands on prior work performed in the DDT-resistant strain 91-R by investigating the structural and expression level (functional) variance across all P450 gene family members compared with that of its control strain, 91-C.…”
Section: Introductionmentioning
confidence: 99%